Correction: Different dry-wet pulses favor different functional strategies: A test using tropical dry forest tree species. - Flor Vega-Ramos; Lucas Cifuentes; Fernando Pineda-García; Todd Dawson; Horacio Paz (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0309510.].